The Illness perception in patients with diabetes mellitus based on characteristics: cross-sectional study - Anita Joeliantina; Indriatie Indriatie; Endang Soelistyowati; Nur Hasanah (International Journal of Advanced Health Science and Technology, 2025)
Disease perception is a factor that affects self-care practices, psychological distress, and other health outcomes in people living with diabetes mellitus (DM). A positive perception of the disease can affect the patient's self-care and health status. This study aims to determine the correlation between characteristic factors and illness perception in patients with DM. This study was correlational research with a cross-sectional approach. The sample size was 175 adult patients with DM recruited from 4 health centres in Surabaya in July–August 2024 using a simple random sampling technique. Data analysis uses linear regression with a significance level of 0.05. This study shows that most (59.42%) patients with DM have a high illness perception. The factors that had a positive correlation with illness perceptions were age (p=0.021), disease history (p=0.027), and comorbidity (p=0.023). Age, disease history, and comorbidities are factors that are positively correlated with illness perception. This must be vigilance for patients at risk of DM, so they are conditioned to perceive the disease positively. As part of health workers, nurses must provide continuous education and counselling about patients' diseases